Factors that influence the used of e-payment: A study on Employee Provident Fund (EPF) customers in Kuantan / Muhammad Zulhelmi Razali - Razali, Muhammad Zulhelmi (2016)
With the establishment and development of EPF institutions, it has helped Malaysian especially to the private sector workers to make a monthly contribution without any hesitation especially when it related to online method. It is due to the EPF nowadays making some continuous improvement whereby the customer can make transaction via online which is e-payment method. Majority of Malaysians are lack of awareness and knowledge regarding the online payment method since online payment method are newly introduced in EPF Kuantan. Therefore, this paper investigates the other factor the influence the used e-payment in term of education, security and advancement of technology, by using questionnaire to gain the data and information. Based on the analysis made, only one of variable shows significant relationship to the factor that influences the used e-payment. However, although the analysis shows two variable of study which are education and advancement of technology showed not significant toward used of e-payment, which means EPF customer do not understand and aware much about it. Hence, it is important to the EPF customer to be more aware on advancement of technology and learn something new